Monogenic disorders of the pancreatic β-cell: Personalizing treatment for rare forms of diabetes and hypoglycemia - van de Bunt, M; Gloyn, A (2007)
Over the past 10-20 years, our understanding of the genetic etiology of monogenic disorders of the pancreatic β-cell has greatly improved. This has enabled clinicians to provide patients with more accurate information regarding prognosis and inheritance and has influenced treatment. Maturity-onset diabetes of the young and neonatal diabetes are two such examples. Patients with maturity-onset diabetes of the young due to glucokinase mutations can usually be managed by diet alone, while those affected by HNF-1α and HNF-4α mutations respond well to low doses of sulfonylureas. The identification of mutations in the ATP-dependent potassium channel genes KCNJ11 and ABCC8 as the most common cause of permanent neonatal diabetes has improved treatment regimes for affected children. In addition to enabling patients to stop insulin injections, their glycemic control has also improved. These advances show the importance of unravelling the genetics of a disease to achieve the best individualized treatment for the patients affected. © 2007 Future Medicine Ltd.